Five-year clinical and radiological outcomes in 257 consecutive cementless Oxford medial unicompartmental knee arthroplasties. (May 2017) - Blaney, J.; Harty, H.; Doran, E.; O'Brien, S.; Hill, J.; Dobie, I.; Beverland, D.
Abstract : Aims: Our aim was to examine the clinical and radiographic outcomes in 257 consecutive Oxford unicompartmental knee arthroplasties (OUKAs) (238 patients), five years post-operatively. Patients and Methods: A retrospective evaluation was undertaken of patients treated between April 2008 and October 2010 in a regional centre by two non-designing surgeons with no previous experience of UKAs. The Oxford Knee Scores (OKSs) were recorded and fluoroscopically aligned radiographs were assessed post-operatively at one and five years. Results: The median age of the 238 patients was 65.0 years (interquartile range (IQR) 59.0 to 73.0), the median body mas index was 30.0 (IQR 27.5 to 33.0) and 51.7% were male. There were no intra-operative complications. There was a significant improvement in the median OKS at six weeks (34, IQR 31.0 to 37.0), one year (38, IQR 29.0 to 43.0) and five years (37, IQR 27.0 to 42.0) when compared with the pre-operative scores (16, IQR 13.0 to 19.0) (all p = < 0.01). No patient had progressive radiolucent lines or loosening. A total of 16 patients had died by five years. The cumulative survival at five years was 98.8% and the mean survival time was 5.8 years (95% confidence interval 5.6 to 5.9). A total of seven OUKAs (2.7%) were revised; three within five years and four thereafter, between 5.1 and 5.7 years post-operatively. Five (1.9%) had re-operations within five years. Conclusion: The proportion of patients requiring revision at five years is lower than that generally reported for UKA. These findings add support for the use of the cementless OUKA outside the design centre. Longer follow-up is required. Cite this article: Bone Joint J 2017;99-B:623–31.